Autotaxin Downregulates LPS‐Induced Microglia Activation and Pro‐Inflammatory Cytokines Production. Issue 12 (15th October 2014) - Awada, Rana; Saulnier‐Blache, Jean Sébastien; Grès, Sandra; Bourdon, Emmanuel; Rondeau, Philippe; Parimisetty, Avinash; Orihuela, Ruben; Harry, G. Jean; d'Hellencourt, Christian Lefebvre
ABSTRACT Inflammation is essential in defense against infection or injury. It is tightly regulated, as over‐response can be detrimental, especially in immune‐privileged organs such as the central nervous system (CNS). Microglia constitutes the major source of inflammatory factors, but are also involved in the regulation of the inflammation and in the reparation. Autotaxin (ATX), a phospholipase D, converts lysophosphatidylcholine (LPC) into lysophosphatidic acid (LPA) and is upregulated in several CNS injuries. LPA, a pleiotropic immunomodulatory factor, can induce multiple cellular processes including morphological changes, proliferation, death, and survival. We investigated ATX effects on microglia inflammatory response to lipopolysaccharide (LPS), mimicking gram‐negative infection. Murine BV‐2 microglia and stable transfected, overexpressing ATX‐BV‐2 (A +) microglia were treated with LPS. Tumor necrosis factor α (TNFα), interleukin (IL)‐6, and IL‐10 mRNA and proteins levels were examined by qRT‐PCR and ELISA, respectively. Secreted LPA was quantified by a radioenzymatic assay and microglial activation markers (CD11b, CD14, B7.1, and B7.2) were determined by flow cytometry. ATX expression and LPA production were significantly enhanced in LPS treated BV‐2 cells. LPS induction of mRNA and protein level for TNFα and IL‐6 were inhibited in A+ cells, while IL‐10 was increased. CD11b, CD14, and B7.1, and B7.2 expressions were reduced in A+ cells. Our results strongly suggest deactivation of microglia and an IL‐10 inhibitory of ATX with LPS induced microglia activation. J. Cell. Biochem. 115: 2123–2132, 2014. © 2014 Wiley Periodicals, Inc.